THE ROLE OF LEARNING INTENSITY AS A MEDIATOR OF THE INFLUENCE OF TEACHER COMPETENCY AND PERSONAL TALENT ON DANCE SKILL - Putri, Ria Safira; Daryono, Rihab Wit (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Teacher competency and personal talent are often considered as the main factors in the development of students' dance skills. However, learning intensity can also play an important role in mediating the influence of both factors. Learning intensity refers to the stage of involvement, dedication, and effort devoted by individuals in the learning process. This study aims to examine the role of learning intensity as a mediator in the influence of teacher competency and personal talent on students' dance skills. This research method is a survey method with a quantitative approach. The number of samples taken was 60 students from dance extracurriculars at MI Kresna. Data were collected through a questionnaire from a Likert scale with 4 alternative answers. PLS-SEM analysis was used to analyze the data and test and evaluate the construction of problem-solving ability measurement variables. The results showed that teacher competency on learning intensity (β = 0.261); (ρ = 0.005) and learning intensity on dance skills (β = 0.263); (ρ = 0.310) had no significant effect. In addition, learning intensity was proven to mediate the influence of personal talent (β = 0.155); (ρ=0.376) and teacher competency (β=0.069); (ρ=0.324) towards dance skill. Implications of increasing learning intensity in mediating the influence of teacher competency and personal talent with students' dance skills in dance material from dance extracurricular at MI Kresna. The recommendations of this study include providing training that focuses on teacher awareness and motivation in utilizing personal talents effectively. Thus, this study is expected to significantly improve teacher competency, personal talents, and students' dance skills in arts and culture